Erratum (Academy of Management Journal, 2007)
The article presents a correction to an article entitled “Boundary Spanners” Identification, Intergroup Contact, and Effective Intergroup Relations,' by Andreas Richter, Michael A. West, Rolf van Dick, and Jeremy F. Dawson, previously published in the December 2006 issue.